2021
DOI: 10.2174/1573397116666201029155856
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Autoimmune Diseases: A Systematic Review of Reported Cases

Abstract: Introduction: Over 4.9 million cases of Coronavirus disease 2019 (COVID-19) have been confirmed since the worldwide pandemic began. Since the emergence of COVID-19, a number of confirmed cases reported autoimmune manifestations. Herein, we reviewed the reported COVID-19 cases with associated autoimmune manifestations. Methods: We searched PubMed database using all available keyword for COVID-19. All related studies between January 1st, 2020 to May 22nd, 2020 were reviewed. Only studies published in English l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 39 publications
1
55
0
2
Order By: Relevance
“…Of note, these manifestations are generally seen in subjects with minimal or not lung disease pointing towards a hyperactive immune response which, while being protective against pneumonia, can lead to collateral damage to other organ systems. Natural infection has also been associated with case reports of vasculitis, neurological disease including GBS and others in addition to other occasionally reported IMDs [ 45 , 46 , 47 ]. Herein, we report a wide variety of vaccine-associated flares or new-onset in IMDs ranging from autoinflammatory, mixed pattern disease (BD) and autoimmune diseases rather than an enrichment in autoimmune diseases that are linked to disordered nucleic acid metabolism and abnormal interferon-stimulated gene signatures involving the TLR-7/9 pathways [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these manifestations are generally seen in subjects with minimal or not lung disease pointing towards a hyperactive immune response which, while being protective against pneumonia, can lead to collateral damage to other organ systems. Natural infection has also been associated with case reports of vasculitis, neurological disease including GBS and others in addition to other occasionally reported IMDs [ 45 , 46 , 47 ]. Herein, we report a wide variety of vaccine-associated flares or new-onset in IMDs ranging from autoinflammatory, mixed pattern disease (BD) and autoimmune diseases rather than an enrichment in autoimmune diseases that are linked to disordered nucleic acid metabolism and abnormal interferon-stimulated gene signatures involving the TLR-7/9 pathways [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study sought to investigate this relationship between SARS-CoV-2 and GBS in the UK, and found that the incidence of GBS had declined during the pandemic, suggesting that SARS-CoV-2 is either not a trigger for GBS in this population, or it is causing fewer cases than are being prevented by the lockdown and new hygiene practices [67]. However, the ability of viral infections to trigger autoimmunity, reports of molecular mimicry between SARS-CoV-2 and human tissues [68], and onset of autoimmunity within a month of first COVID symptoms [66] suggest SARS-CoV-2 may be etiologic for other types of IMIDs, or for GBS in other genetic backgrounds. At present, insufficient data exist to delineate a role of COVID-19 in triggering new onset IMIDs.…”
Section: Does Covid-19 Induce Autoantibodies and Autoimmune Disease?mentioning
confidence: 98%
“…In addition to autoreactive antibodies, there are also case reports of clinical autoimmune diseases post SARS-CoV-2 infection, including autoimmune cytopenia, immune thrombocytopenic purpura, Guillain-Barre syndrome (GBS), Miller Fisher syndrome, and acute disseminated encephalomyelitis [8,66]. While these case reports are informative, they are limited by reporting bias, and it is difficult to determine if these patients would have otherwise developed IMIDs without SARS-CoV-2 infection, and therefore whether these findings are coincidence, rather than causation.…”
Section: Does Covid-19 Induce Autoantibodies and Autoimmune Disease?mentioning
confidence: 99%
“…Кроме того, по мере прогрессирования пандемии COVID-19 появлялись различные сообщения о развитии аутоиммунных заболеваний после того, как инфекция взята под контроль [48,49]. Так, после попадания в эпителиальные клетки респираторного тракта коронавируса SARS-CoV-2, вызывающего заболевание, у некоторых пациентов наблюдается тяжелое состояние, связанное с гиперергическим воспалением и обозначаемое как цитокиновый шторм, а также развитие тромботических явлений.…”
Section: Reviewunclassified